2020
DOI: 10.1155/2020/8822994
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Higher Performance and Less Thickness Concrete Pavement: Using a Nonconventional Concrete Mixture

Abstract: During the last three decades, concrete pavement or rigid pavement became a widely used alternative of flexible pavement (asphalt pavement) at freeways and highways with high traffic of heavy vehicles, due to its durability, long life, and less need of maintenance; however, the cost of construction for rigid pavement is very high compared to asphalt pavement. Developing a new concrete mixture to increase the performance and reducing the required thickness of concrete pavement became an important issue in rigid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Comparing concrete pavement and asphalt pavement it is found that concrete pavement is more expensive but suitable for a higher traffic intensity. Because concrete pavement requires lower maintenance frequencies and a less amount of thickness of concrete is required for higher traffic intensities [27].…”
Section: Introductionmentioning
confidence: 99%
“…Comparing concrete pavement and asphalt pavement it is found that concrete pavement is more expensive but suitable for a higher traffic intensity. Because concrete pavement requires lower maintenance frequencies and a less amount of thickness of concrete is required for higher traffic intensities [27].…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have carried out the need to increase displacement and curvature ductilities [3][4][5][6][7][8][9]. On the other hand, in research that seeks to increase the stress-strain in concrete, some of these researchers have attempted in various ways [10][11], including by applying reinforcement using steel fiber to the unconfined concrete members [12][13][14][15][16] and some to the confined concrete members [17][18][19] the results of this study indicate an increase in the stress-strain of concrete due to the use of steel fiber.…”
Section: Introductionmentioning
confidence: 99%
“…Construction industry is the vital sector in Palestine. It is considered an essential requirement for economic activities [1,2].…”
Section: Introductionmentioning
confidence: 99%